2020
DOI: 10.1007/s41825-020-00033-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy consumption between non-inverter and inverter-type air conditioner in Saudi Arabia

Abstract: Interest for air-conditioning systems (ACs) has exponentially expanded worldwide throughout the most recent couple of decades. Countries with booming economies including Saudi Arabia report high growth of sales of room air conditioners. With the expanded (GDP) and warming climates, interest for room air-conditioning systems is required to additionally increment. Meeting the expanded need for electricity energy will be a challenge. Expanded utilization of energy-efficient air conditioners impactsly affects lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The analysis results confirmed that air conditioners were the highest energyconsuming equipment in all the academic departments studied. These results support the findings of a study conducted by previous authors [43][44][45][46][47] where air conditioning systems consume the highest electrical energy in the office or educational building. According to Tables 4 and 5 and Figure 1, From the graph, the air-conditioning and laboratory equipment at MED has a high impact on energy consumption of almost 230,000 kWh and energy bills of more than RM 80,000 per year.…”
Section: Equipment Proposed For Energy Efficiency Improvementsupporting
confidence: 91%
“…The analysis results confirmed that air conditioners were the highest energyconsuming equipment in all the academic departments studied. These results support the findings of a study conducted by previous authors [43][44][45][46][47] where air conditioning systems consume the highest electrical energy in the office or educational building. According to Tables 4 and 5 and Figure 1, From the graph, the air-conditioning and laboratory equipment at MED has a high impact on energy consumption of almost 230,000 kWh and energy bills of more than RM 80,000 per year.…”
Section: Equipment Proposed For Energy Efficiency Improvementsupporting
confidence: 91%
“…AC non-inverter memiliki kompresor yang hanya berfungsi dengan satu kecepatan, yaitu menyala dengan kecepatan penuh atau mati. Ketika suhu ruangan mencapai suhu yang diinginkan, maka kompresor akan mati, dan ketika suhu ruangan meningkat kembali, maka kompresor akan menyala kembali dengan kecepatan penuh [14], [8]. Pada AC inverter kompresor dapat diatur kecepatannya sesuai dengan kebutuhan pendinginan ruangan.…”
Section: Pengumpulan Dan Analisis Dataunclassified
“…Sebuah penelitian lain yang dilakukan pada iklim di Arab Saudi membandingkan efisiensi energi dari berbagai jenis sistem AC yang berbeda dengan memperhatikan konsumsi energi dan kinerja sistem dari empat jenis AC yang berbeda. Hasil penelitian menunjukkan bahwa jenis AC dengan sistem pengaturan suhu otomatis dan teknologi inverter memiliki efisiensi energi yang lebih baik [8] [9]. Membandingkan variabel seperti daya, kapasitas pendinginan, konsumsi energi tahunan, biaya listrik, dan efisiensi pada berbagai merek AC akan memberikan informasi yang transparan tentang efisiensi AC yang tersedia di pasaran [10].…”
unclassified
“…These deviations induce several irreversibilities within the system, necessitating additional power input for the compressor [3]. Extensive research is therefore dedicated to the reduction of power consumption in VCRS [4][5][6][7][8], although energy efficiency alone does not dictate the performance of these systems. The system's capacity to extract heat from the space is equally crucial, an aspect captured by the Coefficient of Performance (COP).…”
Section: Introductionmentioning
confidence: 99%